The Older Adult's Readiness to Achieve Happy Aging in the City of Yogyakarta in 2021 - Daning Widi Istianti; Resta Betaliani Wirata (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
The final stage of the older adult is followed by the change in bodily function such as physical function, mental (cognitive), spiritual, emotions and feelings. The process of aging is a thing to be passed for the older adult. However, real experiences occur differently, depending on how one’s perception about aging, what should be prepared to enter into this process, and factors which may influence the smoothness of the aging process. The older adult has a goal at the end of his life. This is what will determine whether the older adult can reach successful old age or not that can increase their quality of life. To be an older adult efficiently, and capable of participating in government programs, needs to be prepared. To reach success aging in the sense of healthy and happy is the dream of every individual who enters an adult age. This study aims to identify readiness of older adult to face the aging process and the activity done to reach a happy aging. Research methodology used was qualitative with purposive sampling technique. The results of the interviews transcribed in verbatim and analyzed to find the theme. The result revealed six (6) themes 1) the aging is the process of growing old and having physical change, 2) having a daily life with doing activities and preserving health, 3) accepting changes, 4) spending time with the family, 5) having a calm mind without any burden, 6) gathering in peer group. The older adult has good readiness. They are in need of support from various parties, including themself, to able to achieve good and happy old age.